Histomorphological and Immunohistochemical Reappraisal of Cutaneous Adnexal Tumours: A Hospital Based Study - Prakriti Shukla; Uroos Fatima; Anil K. Malaviya (Scientifica)
Background. Diagnosing adnexal tumours of the skin is a challenge due to their wide variety, infrequent occurrence in practice, and confusing morphological picture. Aims and Objectives. The present study aims to observe the spectrum of adnexal tumours at our institute and to evaluate them based on histomorphological, histochemical, and immunohistochemical methods either alone or in combination for proper identification and classification. Materials and Methods. A partly retrospective and partly prospective study was conducted on adnexal skin tumours over a period of 6 years. Relevant clinical profile was recorded. Histopathological examination was carried out and special stains were applied as and when required. Immunohistochemistry was performed where diagnosis with routine stains was not possible. Results. A total of 150 skin tumour biopsies were received. There were 87 keratotic tumours, 39 adnexal tumours, and 24 melanocytic tumours. Amongst the adnexal tumours, 51.3% eccrine, 30.8% follicular, and 17.9% sebaceous tumours were seen. In five cases, histological diagnosis was troublesome where immunohistochemistry helped in making final diagnosis. Limitations. The sample size is small. Conclusion. Histomorphology is confirmatory in majority of the adnexal tumours but few rare lesions that mimic internal malignancy require a panel of immunomarkers to rule out other possible differentials.